Civil Engineering: Perceptions and perspectives of the first class of students of a College in the interior of of Rio Grande do Sul (Research, Society and Development, 2020)
This research aimed to analyze the profile of students entering the first class of the Civil Engineering Course, from a Private College in the interior of Rio Grande do Sul, Brazil. The case study has a qualitative approach. The research instrument was a questionnaire containing twelve questions, based on the theoretical and methodological assumptions of Gil (1991), applied with ten subjects, being students of the present author in the discipline of Elementary Calculus for Engineering. For data analysis, Bardin (2016) was used, which helped the organization of the collection obtained. Through the research, it was possible to see its importance, at this initial moment, with the purpose of getting to know the students and also, the essential continuity of the research throughout the semesters, as a way to accompany the students in their trajectory and to know the new ones.